PENGARUH CORE QUALIT, RELATIONAL QUALITY, PERCEIVED VALUE, CUSTOMER SATISFACTION, SERVICE SWITCHING DAN VOICE TERHADAP LOYALITY PADA KANTOR KONSULTAN PAJAK HUSNI & MULYADI CONSULTING - Sunandar Sunandar; Hesti Widianti; Erni Unggul Sedya Utami (P4M STIE Putra Bangsa, 2016)
ABSTRACT This study aimed to determine whether the core quality, relational quality, perceived value, customer satisfaction service, switching and voice significant effect partially and simultaneously to loyality to the Office of Tax Consultants Husni & Mulyadi Consulting and to determine which variables most influence on loyalty in Husni & Mulyadi Tax Consulting among core quality, relational quality, perceived value, customer satisfaction, service switching and voice. Some of the benefits expected from the results of this research that the researchers expected to improve the knowledge of scientific thinking and the ability to analyze a problem, especially with regard to core quality, relational quality, perceived value, customer satisfaction service, switching and voice effect on loyalty. The results of the regression test core quality, relational quality, perceived value, and customer satisfaction was significantly partially loyality to the Office of Tax Consultants Husni & Mulyadi Consulting. While the service switching and voice no significant effect partially on loyality to the Office of Tax Consultants Husni & Mulyadi Consulting. Core quality variable, relational quality, perceived value, customer satisfaction, service switching, and voice simultaneously significant effect on loyalty to the Office of Tax Consultants Husni & Mulyadi Consulting. Relational quality variables are variables that most influence on loyalty to the Office of Tax Consultants Husni & Mulyadi Consulting.